Association between thyroid dysfunction and insulin resistance: a retrospective cohort study - Qi Song; Hari Krishnamurthy; Tianhao Wang; Karthik Krishna; Chithra Suresh; Thushani Siriwardhane; Vasanth Jayaraman; Kang Bei; John J Rajasekaran (BMJ Open)
Objective To evaluate the association between thyroid disease and diabetes markers.Design Retrospective cohort study.Setting The study was conducted in a diagnostic setting where the primary care providers recommended the patients to test for thyroid and diabetes panels.Participants The thyroid and diabetes markers were tested in 32 787 subjects with suspected thyroid and related conditions who visited Vibrant America Clinical Laboratory between January 2015 and June 2019.Results Our general prevalence results showed that homeostatic model assessment-insulin resistance (HOMA-IR) was elevated in overt hypothyroid subjects (43.7%) and overt hyperthyroid subjects (42.2%). Glycated hemoglobin (HbA1C) was elevated in subclinical hypothyroid subjects (19.2%), overt hypothyroid subjects (22.3%) and overt hyperthyroid subjects (21.2%). Glucose was significantly elevated in subclinical hypothyroid subjects (24.2%) and overt hyperthyroid subjects (31.0%). Insulin was significantly elevated in overt hypothyroid subjects (15.1%). Interestingly, we found that 70.3% of subjects who had their HOMA-IR score escalated from negative (HOMA-IR<2.7) to positive (HOMA-IR>2.7) during their multiple visits had anti-thyroid peroxidase (anti-TPO) 369 (±242) days prior to the onset of this change.Conclusion Our findings showed that anti-TPO levels are elevated before the onset of insulin resistance, indicating its potential use as a predictive marker.